2019
DOI: 10.1016/j.omto.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Dendritic Cell Therapy in Solid Tumors with Immunomodulating Conventional Treatment

Abstract: Dendritic cells (DCs) are the most potent antigen-presenting cells and are the key initiator of tumor-specific immune responses. These characteristics are exploited by DC therapy, where DCs are ex vivo loaded with tumor-associated antigens (TAAs) and used to induce tumor-specific immune responses. Unfortunately, clinical responses remain limited to a proportion of the patients. Tumor characteristics and the immunosuppressive tumor microenvironment (TME) of the tumor are likely hampering efficacy of DC therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 163 publications
(243 reference statements)
0
43
0
1
Order By: Relevance
“…The approvals of immune checkpoint inhibitors for several cancer types and the rapidly growing recognition that immunotherapy significantly improves outcomes for cancer patients led to a re-emergence of cancer vaccines, including dentritic cell (DC)-based immunotherapy [1][2][3][4][5][6][7]. DCs are Pharmaceutics 2020, 12, 210 2 of 10 essential in immunity due to their role in priming, activating, and directing the T cells to target tumor cells and, thereby, by promoting antitumorigenic responses [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The approvals of immune checkpoint inhibitors for several cancer types and the rapidly growing recognition that immunotherapy significantly improves outcomes for cancer patients led to a re-emergence of cancer vaccines, including dentritic cell (DC)-based immunotherapy [1][2][3][4][5][6][7]. DCs are Pharmaceutics 2020, 12, 210 2 of 10 essential in immunity due to their role in priming, activating, and directing the T cells to target tumor cells and, thereby, by promoting antitumorigenic responses [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While the efficacy and immunogenicity of the DC vaccines have been demonstrated by numerous clinical studies, the results have been largely misleading. This can be due in part to functional deficiencies in cells comprising traditional vaccine formulations, which are poorly prepared to resolve the immunosuppressive tumor microenvironment restricting DC and cell activity [15,32]. Our new vaccine made by conjugating the TLR7 agonist SZU-106 to DAC treated AML cells were aimed to target all three key components in the classical immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of cancer vaccines (including DC vaccines) with chemotherapy has also been explored in the clinic (for a review also of ongoing trials see [129][130][131][132]). While significant synergism seems apparent only in few trials, most of them DC studies [133][134][135][136], a negative impact has never been reported, as the rules for a successful combination-also derived from animal studies-have been taken into account.…”
Section: Challenges and Future Perspectives Of DC Vaccine Therapymentioning
confidence: 99%